PENGARUH CEO DUALITY TERHADAP FIRM VALUE DAN EARNINGS QUALITY SEBAGAI VARIABLE INTERVENING - Davin Wijaya; Devie Devie Devie (Business Accounting Review, 2017)
This study aimed to know the direct and significant influence between CEO Duality variable to firm value and earnings quality as intervening variable. The sample used in this research was 43 LQ 45 Companies listed in Indonesia Stock Exchange starting from 2013-2015. The data processed by using smart PLS2 software.The result of the research found negative influence of CEO duality to firm value, negative influence of CEO duality to earnings quality, and positive influence of earnings quality to firm value.